EXAMINING THE FINANCE- GROWTH NEXUS IN CAMEROON USING COINTEGRATION APPROACH - Ngimanang, Achamoh (American Journal of Economics, 2020)
Purpose: This study explores the empirical relationship between growth rate of real GDP and financial development using Cameroons time series data spanning from 1978 to 2017. Methodology: After shedding light to the evolution of financial development in Cameroon and exploring some relevant literature, the study assesses the finance-growth linkages in Cameroon by specifying and estimating the long run and short run functions for financial development using cointegration and Error Correction modeling (ECM) techniques in addition to Engle and Granger causality testing. Findings: Growth of real GDP used in this paper to capture economic growth was reported to have a positive and highly significant relationship with the variable for financial development and the relation was more significant in the short run than in the long run after controlling for other variables. Bidirectional causality was also noticed between the two set of variables. Unique contribution to theory, practice and policy: Results of this paper suggests that financial sector of Cameroon can efficiently allocate credit to the private sector as an indicator of financial development by stimulating economic activities with the aim of raising gross domestic product of the country in both short and long run. Keywords: Economic growth, financial development, cointegration, Cameroon